PENGARUH SISTEM PERPAJAKAN DAN SANKSI PAJAK TERHADAP PERSEPSI PENGGELAPAN PAJAK DIMODERASI PREFERENSI RESIKO - Luh Putri Mas Mirayani; RR. Maria Yulia Dwi Rengganis (Faculty of Economics and Business, Universitas Warmadewa, 2023)
The taxation system in Indonesia, namely the self-assessment system, requires taxpayers to do their own tax reporting and this is prone to evasion by taxpayers. However, on the other hand, preventive tax sanctions are used as an effort to prevent this. There are inconsistent results from previous studies related to the tax system and tax sanctions on perceptions of tax evasion, so risk preference is used as a moderating variable. Risk preference is the extent to which taxpayers dare to take risks in terms of tax reporting. These three things are closely related to the perception or intention of the taxpayer to commit or not to commit tax evasion. This research was conducted on individual taxpayers at KPP Pratama South Badung. The type of data used is primary data obtained through distributing questionnaires. The sample used is 100 respondents determined by the Slovin formula. The analysis technique used is moderated regression analysis. The results showed that the taxation system has a positive effect on perceptions of tax evasion. Tax sanctions have a negative effect on perceptions of tax evasion, risk preferences are unable to moderate the influence of the tax system on perceptions of tax evasion, and risk preferences strengthen the relationship between tax sanctions and perceptions of tax evasion